Pengaruh Motivasi, Disiplin Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt Bisa Inti Sarana Di Kota Batam - Nuraeni, Brigida Endah (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2022)
The review of this research is the influence of motivation, discipline and working environment toward performance of the employee. Object of research is the employee of PT Bisa Inti Sarana. The purpose of the research is to determine if the motivation, discipline and working environment affect the employee’s working performance.60 employees of PT Bisa Inti Sarana have been taken as the sample of this research, using Saturation Sampling Technique based on the Non-probability Sampling. Data collection is done by distributing questionnaires. The result of the research shows that motivation and work environment partially have positive and significant effect to employee's performance, but discipline has influence no significant effect, while motivation, discipline and work environment simultaneously affect employee performance.From the result of the regression analysis, it is obtained the value of coefficient of determination (R2) which is 0,880, which means that 88% of the performance of the employee is affected by motivation, discipline and environment variables. As for the rest of 12% is affected by the other variables that is not examined in this research.